Pengaruh Zat Pengatur Tumbuh Organik terhadap Pertumbuhan Benih Tomat (Lycopersicum esculentum Mill.) yang Bersumber dari Hasil Panen Petani - Marlina Marlina (Fakultas Pertanian, Universitas Timor, 2023)
The study aims to determine the effect of Growth Regulatory Substances (GRS) on the growth of tomato seeds of farmers' harvests. The research method used a completely randomized design non-factorial with three replications. The factors studied were Organic Growth Regulators consisting of bean sprout extract, onion extract and young coconut water with a concentration of 50% each. The variables observed were growth potential, germination rate, growth speed, growth synchronously, and seed vigor. The results showed that young coconut water with a concentration of 50% gave the best results at the rate of growth potential with a percentage of 95.83% and seed vigor with a percentage of 91.66%, while the best germination was found in onion extract with a percentage of 83.33%, while the best growth uniformity was found of bean sprout extract with a percentage of 75.00%. However, it can be concluded that organic PGR did not significantly affect the growth rate of tomato seeds.